An Impact Analysis of Testability Model - Srivastava, Kavita (International Journal of Computer Sciences and Engineering, 2018)
Testability is not new term as quality issues for software issues. In order to test the software product, the quality of their software product must be using measuring. Testability is the impact analysis the software product imminent requirement. On the behalf of the existing extensive use of software, if used in isolation, testability is oftentimes too fine grained to quantify comprehensively an investigated aspect of the software architecture. This paper calculates the testability index.